THE INFLUENCE OF EDUCATIONAL GAME OF WIRE GAME LINE TROUGHT THE ABILITY OF THE 5-6 YEARS OLD CHILDREN IN RECOGNIZING NUMBERS - Frisca Mudia Hawari; Hukmi Hukmi (Jurnal Educhild : Pendidikan dan Sosial, 2020)
Based on observations in the field, it can be known that knowledge about the concept of numbers in children aged 5-6 years is still in the category of developing, so it is necessary to use APE wire game line. This study aims to understand the effect of the APE wire game line on the ability to recognize the concept of numbers. This research was conducted in Pertiwi Kindergarten Pekanbaru City. This study used an experimental method with one group pretest posttest design with a sample of 13 children and used a saturated sampling purposive. Data collection techniques in this study were observation techniques. The data analysis technique used the t-test using the SPSS 21 program. The results of the data analysis can be obtained t count 23,698 is greater than t table 2.179 with a significance of 0.000 <0.05. It can be concluded that there are differences in knowledge about haze disaster management before and after the use of picture story book media. The influence given by the media illustrated story books based on the N Gain formula of 56,93% was in the medium category.Penelitian ini bertujuan untuk mengetahui pengaruh APE wire game line terhadap kemampuan mengenal konsep bilangan. Penelitian ini dilakukan di TK Pertiwi Kota Pekanbaru. Penelitian ini menggunakan metode eksperimen dengan desain one group pretest posttest dengan jumlah sampel 13 orang anak dan menggunakan teknik sampling purposive. Teknik pengumpulan data dalam penelitian ini adalah dengan teknik observasi. Teknik analisis data menggunakan uji t-tetst dengan menggunakan program  SPSS 23. Hasil analisis data dapat diperoleh t hitung 23,698 lebih besar dari t tabel 2,179 dengan signifikansi 0,000<0,05. Dapat disimpulkan bahwa terdapat perbedaan pengetahuan tentang kemampuan mengenal konsep bilangan sebelum dan sesudah penggunaan APE wire game line. Pengaruh yang diberikan oleh APE wire game line berdasarkan rumus N Gain sebesar 56,93%  berada pada kategori sedang.